"O pontinho da balança" : história do cotidiano de mulheres teuto-brasileiras evangélicas no sul do Brasil, na perspectiva do privado e do público - Dreher, Scheila dos Santos (2007)
In this dissertation I intend to analyze and give visibility to the presence and actuation of German-Brazilian evangelical women in the family, in evangelical congregations and in the society of southern Brazil in private and public perspective, especially between the last quarter of the 19th century and the middle of the 20th century,. Therefore I intend to (re)write a history of the daily life of German-Brazilian evangelical women, considering the daily life as the place of historical being and the interactivity of private and public spaces. In the first chapter I present the theoretical, methodological and analytical basis of this history: I ask about the place of women in the history of German evangelical immigration, I focalize on the private and the public as a perspective of analysis and I raise questions about time delimitation. In the second chapter I seek to recognize that cultural knowledge these women (and men) brought from Germany to the south of Brazil (considering their plural experiences) and that continued to inspire their daily life, in a process of continuities and discontinuities, in a perspective of the new social, economical, political and religious contexts. In this way I approach the experiences of women (and men) examining the reasons which led to the emigration from Germany to Brazil, as well as the definition of private and public in the daily life of German (evangelical) women in the 19th century. Further I examine the experiences that constituted a spirituality of German evangelical women and their initiatives, considering evangelical confession as a differential in their lives. In the third chapter I look at the daily reality which involved German-Brazilian evange1icals, especially about the presence and participation of women in the process between emigration and immigration as well as about the possibilities in their daily life between the private and the public. In the fourth chapter I examine the process of the construction of "a" feminine ethnic and confessional identity, considering the exercise of power by the German-Brazilian evangelical women, even if it was in a logic of submission, because they lived in a patriarchal culture; I examine their relationship to labor within the German-Brazilian evangelical congregation and their activity of preserving Germanism as "mothers of the nation." An analysis of "the" history of the daily life of German-Brazilian evangelical women allows one to glimpse at circumstances, speeches and cultural inheritances that had marked their histories in a process of continuities and discontinuities, and have been constitutive to their identities in a permanent process of construction, differentiation and resignification. It also allows one to visualize an active participation of German-Brazilian evangelical women in family, community and society in southern Brazil, through the exercise of power, even within a logic of submission, in the (possible) private and public spaces and in the seesaw between both of them.